Usynligt? Det professionelle blik på køn og kropslig materialitet i daginstitutioner - Krøjer, Jo (Tidsskrift for Professionsstudier, 2025)
The article addresses questions of gender and bodily materiality and how this is included in professional practice in Danish ECEC. Point of departure is the finding that professionals are required to include gender equality and equal opportunities for all children in the everyday practice in daycare centers. Based on a multi-method, empirical study consisting of observations and research workshops, the article examines the professional perspective that is part of the pedagogical staff's interactions with children in ECEC-institutions. The study shows that the professionals' view of the children has a paradoxical, partial blindness that makes children's gender partially invisible in professional practice. This invisibility becomes a barrier in professionals' work to ensuring gender equality and equal opportunities for all children. However, the analysis also shows how collective reflections can widen the professional view, so that specific gender differences become visible to the professional's view. This way, they can become integrated in professional practice in a way that better ensures gender equality for all children.